O26 Population pharmacokinetic meta-analysis of individual data to design the first randomized efficacy trial of vancomycin in neonates and young Infants. Issue 6 (17th May 2019) - Jacqz-Aigrain, E; Leroux, S; Thomson, AH; Allegaert, K; Capparelli, EV; Biran, V; Simon, N; Meibohm, B; Y-L, Lo; Marqués, R; Peris, J-E; Lutsar, I; et al.
Abstract : Background: In the absence of consensus, the present meta-analysis was performed to determine an optimal dosing regimen of vancomycin for neonates. Methods: A 'meta-model' using NONMEM with 4894 concentrations from 1631 neonates was built and Monte Carlo simulations were performed to design an optimal intermittent infusion, aiming at reaching a target AUC0-24 of 400 mg*h/L at steady state in at least 80% of neonates. Results: A two-compartment model best fitted the data. Current weight, post-menstrual age (PMA) and serum creatinine were the significant covariates for clearance (CL). After model validation, simulations showed that a loading dose (25 mg/kg) and a maintenance dose (15 mg/kg twice daily if < 35 weeks PMA and 15 mg/kg three times daily if ≥ 35 weeks PMA) achieved the AUC0-24 target earlier than a standard 'Blue Book' dosage regimen in more than 89% of the treated patients. Conclusions: The results of a population meta-analysis of vancomycin data have been used to develop a new dosing regimen for neonatal use and assist in the design of the model-based, multinational European trial, NeoVanc. Disclosure(s): Nothing to disclose